Effect of nutrient management on yield, economics, water and energy use efficiency of maize (Zea mays) under conservation agriculture based maize-wheat (Triticum aestivum) system - MEENA, B R; PARIHAR, C M; NAYAK, H S; PATRA, K; RANA, B; ABDALLAH, A M; GAMBHIR, G; RATHI, N; SINGH, V K (The Indian Journal of Agricultural Sciences, 2021)
A field experiment was conducted under long-term conservation agriculture (CA)-based maize (Zea mays L.)-wheat (Tricum aestivum L.)-mungbean (MWMb) system at ICAR- IARI, New Delhi (2017-18 and 2018-19) in split-plot design to compute the yields, economic, water and energy use-efficiency. There were 3-tillage treatment in main-plots and 4-nutrient management options in sub-plots with 3-replications. Results of present study showed that the grain yield of maize was 21.1% higher in CA-based permanent bed (PB) than conventional till (CT) plots. Net returns and net benefit cost ratio in PB plots was higher by 46.1 and 55.4% compared to CT, respectively (2-year mean basis). Two year mean basis water use-efficiency (WUE), net energy output and energy use-efficiency (EUE) were higher by 17.0, 26.3 and 12.5% in PB plots than CT. No significant effect of tillage was observed on N, P and K content (grains and stover). However, the total N, P and K uptake in maize grains and stover was higher by 23.6, 24.5 and 22.4% under PB than CT plots, respectively. Among nutrient management options; 2-year mean basis maize grain yield was 31.6 and 29.7% higher in Green Seeker (GS) guided-N and site specific nutrient management (SSNM) plots than farmers fertilizer practice (FFP), respectively. Net returns and BC ratio were also higher by 51.4-53.4% and 41.35-42.6% in GS guided-N and SSNM than FFP plots, respectively. WUE, net energy output and EUE were also significantly higher in GS guided-N treatment than FFP. Total N, P and K uptake were also significantly higher in GS guided-N and SSNM plots compared to FFP.